2020
DOI: 10.3906/sag-2002-179
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy between bilateral proximal tubal occlusion and total salpingectomy on ovarian reserve and the cholinergic system: an experimental study

Abstract: Compared to G1 and G3, the number of corpus luteum with secondary follicles was significantly lower in G2, whereas the number of ovarian cysts and fibrosis and apoptosis scores increased significantly. The CHRM1 immunoreactivity was significantly lower in G2 than in G1 and G3. Conclusions: Compared to the bilateral proximal tubal occlusion performed by using bipolar cautery, bilateral total salpingectomy in rats leads to a significant damage in ovarian histopathology and the cholinergic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…In the staining, the intensity of the involvement was evaluated by randomly selecting five areas at 400X magnification in each preparation. Uptake intensity was scored semiquantitatively as 0 (−, no involvement ), 1 (+, weak immunoreactivity ), 2 (++, moderate immunoreactivity ), and 3 (+++, strong immunoreactivity ) (Atilgan et al, 2020). The results were summed to arrive at a single value for that slide.…”
Section: Methodsmentioning
confidence: 99%
“…In the staining, the intensity of the involvement was evaluated by randomly selecting five areas at 400X magnification in each preparation. Uptake intensity was scored semiquantitatively as 0 (−, no involvement ), 1 (+, weak immunoreactivity ), 2 (++, moderate immunoreactivity ), and 3 (+++, strong immunoreactivity ) (Atilgan et al, 2020). The results were summed to arrive at a single value for that slide.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, follicle growth and proliferation and ischemia reperfusion injury could also lead to POF (Atilgan et al., 2015 ; Tuncer et al., 2023 ). Other studies had found that ion channels might also have an impact on ovarian reserve and became one of the factors affecting POF (Şanlı et al., 2021 ; Atilgan et al., 2020 ). Moreover, ovarian tissue damage might be related to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized controlled trial of women with hydrosalpinges [ 17 ] indicated lower ovarian reserve, lower numbers of retrieved oocytes, and higher gonadotropin stimulation dosages in patients who underwent salpingectomy compared with those who underwent proximal tubal occlusion. An experimental study revealed that total salpingectomy in rats leads to more significant damage than proximal tubal occlusion in ovarian histopathology and the cholinergic system [ 18 ]. Another study also indicated that the unilateral total salpingectomy procedure can be detrimental to ipsilateral ovarian tissue as a result of ischemia–reperfusion injury [ 19 ].…”
Section: Introductionmentioning
confidence: 99%